EFEKTIVITAS KINERJA PEGAWAI SEKRETARIAT KOMISI PEMILIHAN UMUM (KPU) KOTA BENGKULU DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH KOTA BENGKULU TAHUN 2018 - Yuliana Hartini; Evi Lorita; Bando Amin C. Kader (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
This study aims to determine the Effectiveness of the Performance of secretariat commission for general election (KPU) Bengkulu City on the organization of the Election of Regional Heads (PILKADA) of Bengkulu City in 2018. The Data were collected by using in-depth interviews, observation and documentation. The obtained data were analyzed by means of data reduction, data presentation and conclusion. This is a qualitative-descriptive study which takes two groups as the informants.The informants are categorized as key informant and principal informants. Key informant in this study was the secretary of KPU Bengkulu City while the principal informants were the secretariat staff of KPU Bengkulu City. The researcher chose the secretary of KPU as the key informant because he knew and mastered the information needed by the researcher. Meanwhile, the secretariat staff of KPU Bengkulu City were selected as the principle informants because they can provide information about organizing the election. The result shows that the performance of the employees of the Secretariat of the General Election Commission (KPU) of Bengkulu City was quite effective in completing the Election of Regional Heads (PILKADA) in 2018.The election run successfully and on time as it is expected.